2021
DOI: 10.1155/2021/5522928
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation: A Study on Predicting the Outbreak of COVID-19 in Saudi Arabia

Abstract: The novel coronavirus disease (COVID-19) has resulted in an ongoing pandemic affecting the health system and economy of more than 200 countries worldwide. Mathematical models are used to predict the biological and epidemiological tendencies of an epidemic and to develop methods for controlling it. In this work, we use a mathematical model perspective to study the role of behavior change in slowing the spread of COVID-19 in Saudi Arabia. The real-time updated data from March 2, 2020, to January 8, 2021, were co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Individuals can protect themselves, their families, and communities by social distancing, wearing face masks, washing hands frequently, and most importantly getting vaccinated. Mathematical models conducted exclusively in the Saudi population to predict biological and epidemiological predispositions toward COVID-19 found that social distancing, personal hygiene, and travel restrictions were vital measures to prevent the outbreak's spread ( 9 ). Evaluating whether individuals aware, embrace, or ignore these measures can provide authorities with insight into how open a given community or region is to adopting measures to deal with the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals can protect themselves, their families, and communities by social distancing, wearing face masks, washing hands frequently, and most importantly getting vaccinated. Mathematical models conducted exclusively in the Saudi population to predict biological and epidemiological predispositions toward COVID-19 found that social distancing, personal hygiene, and travel restrictions were vital measures to prevent the outbreak's spread ( 9 ). Evaluating whether individuals aware, embrace, or ignore these measures can provide authorities with insight into how open a given community or region is to adopting measures to deal with the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…When a person has been infected but is not exhibiting symptoms, that time is referred to as the incubation phase. It makes sense to represent the pandemic using a different compartment representing exposed humans without virus spreaders because the coronavirus sickness has a protracted incubation period [22]. In the SEIR model, it is assumed that the population s size is fixed and that there are no important dynamics during the long duration.…”
Section: Methodsmentioning
confidence: 99%
“…Any numerical method can be used to solve the aforementioned set of equations (22)(23)(24)(25), and the behavior of SARS-Cov-2 can be predicted via simulation. The aforementioned system of equations can be expressed when discrete time ∆𝜏 is involved, shown as follows:…”
Section: Susceptible Exposed Infectious Recovered (Seir) Modelmentioning
confidence: 99%
“…The bilinear incidence rate βSI is considered a mass action incidence, and it is considered to be correct in the early stages of an outbreak of diseases or a huge number of the population. During the recent COVID-19 pandemic, this incidence rate was widely adopted [1]. However, this is insufficient for many epidemics.…”
Section: Introductionmentioning
confidence: 99%